PEMBERDAYAAN PENYULUH DALAM MENINGKATKAN PELAYANAN KEAGAMAAN DI KABUPATEN LAMONGAN PROVINSI JAWA TIMUR - Ayatullah Humaeni; Zaenal Abidin (Harmoni, 2014)
This study was conducted to assess whether the government’s efforts succeeded in increasing the competence of religious counselor so that their duty on religious services runs effectively and optimally. Some important points to be examined in this study, are as follows: How does the implementation of regulations on Functional position of the religious counselor and its credit figure? How the empowerment effort which did by the government in increasing the competence of religious counselor? What factors are driving and inhibiting the religious counselor in carrying out its duties and functions? How do people’s perceptions and expectations toward the religious counselor in performing its duties and functions?